أثر موقف الشنقيطي العقَدي في توجيه إعراب القرآن الكريم: Arabic Grammar, Iâ€˜rab al-Quran, Tasfsir, Aqeedah, Shanqiti - Syed Mohamed, Syed Shahridzan; Seman, Hj. Mohammad (Al-Ḍād Journal, 2019)
This study explains the effect of Shanqiti’s beliefs on the determination of the i’rāb verses of the Qur’an that are disputed by the ulama of tafsir and Arabic grammar. This study focuses on Shanqiti’s essay entitled “Adwa ’al-Bayān Fi Idāḥ al-Qurān bi al-Qurān", whereby it covers the Arabic syntactic problems in sentences that affect the meaning. This study is an applied study in the determination of i’rāb which has various forms and paths that affect the meaning of the verse within the context of Shanqiti, especially with respect to the problems of aqeedah. This study is also a debate on the words in the Quranic verses that are related to i’rāb, as well as the words that do not have clear signs of i’rāb. In addition, this research also studies the verses that have various syntactic positions / i’rāb. Furthermore, this study assesses the choice (tarjih) of an i’rāb position that is influenced by the thought of Syaqiti’s aqeedah.